Late Triassic orogenic assembly of the Tibetan Plateau: constraints from magmatism and metamorphism in the East Lhasa terrane - Chen, Y; Zhang, Z; Palin, RM; Tian, Z; Xiang, H; Dong, X; Ding, H; Qin, S; Li, Y (Oxford University Press, 2021)
The early Mesozoic evolution of the Lhasa terrane, which represents a major component of the Himalayan-Tibetan orogen, remains highly controversial. In particular, geological units and events documented either side of the eastern Himalayan syntaxis (EHS) are poorly correlated. Here, we report new petrological, geochemical and geochronological data for cogenetic peraluminous S-type granites and metamorphic rocks (gneiss and schist) from the Motuo-Bomi-Chayu region of the eastern Lhasa terrane, located on the eastern flank of the EHS. Zircon U-Pb dating indicates that these units record both Late Triassic magmatic (216-206 Ma) and metamorphic (209-198 Ma) episodes. The granites were derived from a Paleoproterozoic crustal source with negative zircon ϵHf(t) values (-5·5 to -16·6) and TDM2 model ages of 1·51-1·99 Ga, and are interpreted to have formed by crustal anatexis of nearby metasediments during collisional orogeny and crustal thickening. The gneisses and schists experienced similar upper amphibolite-facies peak metamorphism and associated partial melting, followed by decompressional cooling and retrograde metamorphism. These rocks were buried to lower-crustal depths and then exhumed to the surface in a collisional orogenic setting during plate convergence. From comparison of these data with those for other metamorphic belts with similar grades and ages, and association of coeval granitic magmatism widespread in the central-east Lhasa terrane, we propose that the studied cogenetic magmatism and metamorphism in the Motuo-Bomi-Chayu region records Late Triassic accretion of the North Lhasa and South Lhasa terranes, which represents the first evidence of the Paleo-Tethys Ocean closure in this part of Asia. These data provide new constraints on the spatial and temporal evolution of the Paleo-Tethyan Wilson Cycle and provide a 'missing link' to correlate the geology and tectonic history of the Lhasa terrane continental crust on either side of the EHS.